Atom‐Efficient Gold(I)‐Chloride‐Catalyzed Synthesis of α‐Sulfenylated Carbonyl Compounds from Propargylic Alcohols and Aryl Thiols: Substrate Scope and Experimental and Theoretical Mechanistic Investigation. Issue 52 (22nd November 2013) - Biswas, Srijit; Dahlstrand, Christian; Watile, Rahul A.; Kalek, Marcin; Himo, Fahmi; Samec, Joseph S. M.
Abstract Gold(I)‐chloride‐catalyzed synthesis of α‐sulfenylated carbonyl compounds from propargylic alcohols and aryl thiols showed a wide substrate scope with respect to both propargylic alcohols and aryl thiols. Primary and secondary aromatic propargylic alcohols generated α‐sulfenylated aldehydes and ketones in 60–97 % yield. Secondary aliphatic propargylic alcohols generated α‐sulfenylated ketones in yields of 47–71 %. Different gold sources and ligand effects were studied, and it was shown that gold(I) chloride gave the highest product yields. Experimental and theoretical studies demonstrated that the reaction proceeds in two separate steps. A sulfenylated allylic alcohol, generated by initial regioselective attack of the aryl thiol on the triple bond of the propargylic alcohol, was isolated, evaluated, and found to be an intermediate in the reaction. Deuterium labeling experiments showed that the protons from the propargylic alcohol and aryl thiol were transferred to the 3‐position, and that the hydride from the alcohol was transferred to the 2‐position of the product. Density functional theory (DFT) calculations showed that the observed regioselectivity of the aryl thiol attack towards the 2‐position of propargylic alcohol was determined by a low‐energy, five‐membered cyclic protodeauration transition state instead of the strained, four‐membered cyclic transition state found for attack at the 3‐position. Experimental data and DFT calculations supported that the second step of the reaction is initiated by protonation of the double bond of the sulfenylated allylic alcohol with a proton donor coordinated to gold(I) chloride. This in turn allows for a 1, 2‐hydride shift, generating the final product of the reaction.